Bahasa Inggris Sebagai Pendidikan Karakter pada Full Day School di Madrasah Aliyah - Nazri, M. Adib; Nursaly, M. Adib Rismarini; Murcahyanto, Hary; Ernawati, Titin (JOEAI (Journal of Education and Instruction), 2021)
This study aims to describe the implementation of full day school in English lessons as character education in Madrasah Aliyah. A qualitative descriptive method was used in this study and carried out at Madrasah Aliyah 2 Wanasaba. Data were taken from principals of madrasah, teachers and staff, class XII students, alumni, and guardians of students. Collecting data using interview, observation, and documentation methods. From the results of research and analysis, it was found that Madrasah Aliyah Negeri 2 Wanasaba implemented full day school from 06.30-17-00 WIB. Full day school is an attempt to implement character education through a merger between the curriculum of the Ministry of National Education and the Ministry of Religion. In conclusion, full day school is a method that is applied to train and familiarize students to become a generation that has independent, religious characters, and has the skills to hone the potential of highly competitive students. are independent, creative, action-oriented, result-oriented, leadership, and hard work. Keywords: Full day school, Character education, English